Effects of COVID-19 on mortality: A 5-year population-based study in Oman. (March 2021) - Al Wahaibi, Adil; Al-Maani, Amal; Alyaquobi, Fatma; Al Harthy, Khalid; Al-Jardani, Amina; Al Rawahi, Bader; Al-Abri, Seif
Highlights: There is 15 % excess mortality in 'all-cause mortality' in Oman during the study period, mainly in the >60-year-old age group. 66 % of the excess death during the study period was attributed to COVID-19. Excess mortality was found in the respiratory, infectious and unclassified diseases. This excess mortality re-enforces the importance of a holistic approach in managing the syndemic effects of COVID-19. Abstract: Background: Mortality surveillance provides a crucial method for monitoring disease activity. Coronavirus disease 2019 (COVID-19) can cause excess mortality both directly and indirectly by increasing deaths from other diseases. The aim of this study was to investigate the effects of COVID-19 on mortality in Oman. Methods: A cross-sectional retrospective analysis of mortality data from 1 January 2015 to 16 August 2020 was undertaken. Baseline mortality estimated using the Farrington flexible model and excess mortality were calculated for the pandemic period (16 March–16 August 2020) according to cause of death, place of death and age group. Results: During the pandemic period, there was a 15% [95% confidence interval (CI) 14–17] increase in all-cause mortality from baseline. When classifying by cause, there was a 9% (95% CI 5–12) increase in deaths due to respiratory diseases, a 2% (95% CI 1–4) increase in deaths due to infectious diseases and a 9% (95% CI 8–11) increase in unclassified deaths. In terms of place of death, 12% (95% CI 11–14) of excess mortality occurred in hospitals and 7% (95% CI 5–8) occurred in homes during the pandemic period. Patients aged >60 years recorded a 15% (95% CI 13–16) increase in all-cause mortality during this period. Conclusion: The COVID-19 pandemic has resulted in a 15% increase in all-cause mortality in Oman, mainly as a result of deaths from COVID-19. However, unclassified deaths, deaths due to respiratory diseases and deaths due to infectious diseases have also increased, enforcing the need for a holistic approach and appropriate coordination of health services during such health crises.